The Effect of Sperm DNA Fragmentation on In Vitro Fertilization Outcomes for Women With Polycystic Ovary Syndrome - Wang, Huan; Li, Hui; Zhu, Jing; Xu, Jianmin; Jiang, Yuqing; Chen, Wenhui; Sun, Yingpu; Yang, Qingling (Frontiers in Endocrinology, 2022)
Background Polycystic ovary syndrome (PCOS) is a prevalent endocrine disease in reproductive women associated with poor pregnancy outcomes. In modern society, people pay more attention to the female factor, but it is uncertain whether sperm quality is another factor affecting pregnancy outcomes of patients with PCOS. Method The effect of sperm DNA fragmentation (SDF) on oocyte fertilization, embryonic development, and pregnancy outcomes for patients with PCOS who underwent in vitro fertilization (IVF) treatment was studied. A total of 141 PCOS patients and 332 control patients undergoing IVF treatment were recruited from January 2017 to December 2019. All female patients were designated into two groups according to the Rotterdam criteria. Each group was divided into two sets, DNA fragmentation index (DFI) ≤15% and DFI > 15%, on the basis of sperm DFI. Result There were no differences in basic clinical characteristics between couples with a sperm DFI ≤ 15% or DFI > 15%. For control patients, no differences were observed in IVF outcomes. However, for PCOS patients, although there were no differences in the fertilization (60.4% vs. 59.9%, p = 0.831), high-quality embryo (68.5% vs. 67.9% p = 0.832), clinical pregnancy (78.4% vs. 66.7%, p = 0.148), and abortion (12.5% vs. 11.5%, p = 1.000) rates, a significantly lower high-quality blastocyst formation rate (26.3% vs. 16.3%, p = 0.023) was observed for couples with a sperm DFI > 15% compared with a sperm DFI ≤ 15%. Conclusion For PCOS patients undergoing IVF, oocytes fertilized using sperm with higher DFI led to a lower high-quality blastocyst formation rate but had no influence on fertilization, high-quality embryo, clinical pregnancy, and miscarriage rates.